Was 2024 a good year for you? Let’s review your yardsticks… - TAN, Seow Hon (Institutional Knowledge at Singapore Management University, 2024)
This op-ed encourages all to reflect on their year and examine whether they have lived meaningfully according to their yardstick of meaning, the legacy they want to leave behind, and whether their talents and credentials are empowering and enabling, rather than restricting them. It is written as part of a research project examining success and flourishing in Singapore.